Multi-argument Control Mode Switching Strategy for Adaptive Cruise Control System. (2016) - Zhenhai, Gao; Jun, Wang; Hongyu, Hu; Wei, Yan; Dazhi, Wang; Lin, Wang
Abstract: Adaptive Cruise Control system contains the distance control function which is an extension of the conventional Cruise Control system. ACC system has to switch to appropriate control modes according to different traffic scenes. The existing switching strategies are generally designed based on two arguments including relative distance and relative velocity between the host vehicle and the preceding vehicle. Because switching thresholds of the existing methods are mostly determined based on steady states of control mode, the switching process cannot be continuous and smooth in many cases. In order to overcome the shortage of existing switching strategy, a new switch strategy is put forward in this paper which considers three arguments: distance, relative velocity and acceleration. This new strategy can make vehicle acceleration continuous and smooth during control mode switching, which improves the comfort performance of ACC system. Moreover, the decision algorithms of cruise mode, follow mode and approach mode in ACC system are built. The new switching strategy with three arguments is established in this paper. At last, the road tests show that the proposed switching strategy is able to switch to correct control mode according to actual traffic scenes. In addition, the switching progress is smoother than the existing two arguments switching strategy.